Kontribusi Karya Tulis Kiai Basori Alwi Terhadap Pengembangan Wawasan Keagamaan Masyarakat - Amrullah, Abdul Malik Karim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
The community is the big institution in the kiai’s perception that must be educated base on good values which are suitable for their life. The syari’ah and tasawuf are studied and needed by moslem community, because both of the subject contribute to sove when the moslem community have problem that ussualy happen in the daily of social life. Kiai Basori Alwi is one of kiai’s who gives solution to the moslem community with his own manuscript that has been writen when moslem people has problems. Kiai Basori Alwi has a motif to develop student achievement, transform religion knowledge to social community and develop curriculum of pesantren, and keep islamic tradition through his manuscript.